Fuzzy weights in data envelopment analysis. - Mansourirad, Ehsanollah; Abu Bakar, Mohd Rizam; Lee, Lai Soon; Jaafar, Azmi (Hikari Ltd, 2010)
In many real problems of evaluating efficiency score for decision making units (DMUs) using data envelopment analysis (DEA) factor weights related to the data may have fuzzy essence and it is required to create methods for solving these problems. In this paper we have provided a method to solve a CCR model with fuzzy weights in the objective function. This method is based on parametric linear programming which is transformed using t-cut concept for fuzzy numbers. Besides our method is based on two steps to find the triangular fuzzy number as weights of the objective function.